Fetal surgery and maternal cortisol response to stress. The myelomeningocele sheep model. (16th February 2016) - Pelizzo, Gloria; Bellieni, Carlo Valerio; Dell'Oste, Clara; Zambaiti, Elisa; Costanzo, Federico; Albertini, Riccardo; Campagnol, Marino; De Silvestri, Annalisa; Calcaterra, Valeria
Abstract: Background : Prenatal surgery represents a multifactorial stressor event for mother and fetus. The stress response to fetal surgery was evaluated by measuring maternal plasma and amniotic fluid (AF) cortisol levels in the myelomeningocele (MMC) sheep model. Subjects and methods : Pregnant ewes ( n  = 8) underwent general anesthesia for MMC-induction (step 1: 75 d gestation), surgical defect repair (step 2: 110 d gestation), and delivery (step 3: 140 d gestation). Maternal blood samples were taken before surgery (surgical stage T1), after laparotomy and uterine exposure (surgical stage T2), at the end of the procedure (surgical stage T3). Fetal stress was evaluated by measuring cortisol levels in AF after hysterotomy at steps 1–3. Results : Maternal cortisol concentrations at T2 and T3 increased compared with T1 ( p  = 0.019 and p  = 0.046). AF cortisol response increased from 1 to 3 surgical steps and during pregnancy. The AF cortisol level was lower than maternal serum levels (induction p  < 0.001; repair p  < 0.001; caesarean section p  < 0.001). Conclusions : Hysterotomy was the most stressful event in the ewes. Fetuses seemed to be partially protected from the high maternal cortisol levels. The fetal stress response to prenatal surgery increased with gestational age. Pain perception development, fetal maturation, and "pain memory" are probably associated with this increase.